Baltic States in NATO: Results of the Decade - V. V. Vorotnikov (MGIMO University Press, 2014)
In the post-Soviet period participation in NATO was one of the major goals of euro-atlantic integration for the Baltic states. Political leaders of Estonia, Latvia and Lithuania have considered participation in the alliance as an important element of euro-atlantic solidarity which allows small - from all viewpoints - states claim decision-making over global issues. This satisfies demands of the political elites and victimized public consciousness for more security, makes it possible for elites to consider their states as bulwark against Russia. Throughout the whole decade, such reasoning has been reflected in doctrines and speeches of Baltic politicians. After joining NATO, the Baltic states became the most active supporters of a deeper integration in the military area and "open door" policy. They have continued reforming their armed forces and renovating military infrastructure. They have acquired "specialization" within NATO by establishing centers of excellence. In terms of euro-atlantic solidarity, the participation in the International Security Assistance Force in Afganistan has become the most important international project for the Baltic states. However, only Estonia managed to mount their defence expenses to the level of 2% GDP. During the „Ukranian crisis" the issue of Baltic membership in NATO acquired special importance. Confrontational rhetoric and appeals to "Russian threat" in Estonia, Latvia and Lithuania, on the one hand, make it possible for their political leaders to constantly demonstrate their importance in the eyes of Western partners and demand more activity of the alliance and, on the other hand, make ground for the political elites to consolidate the electorate, by that ensuring that the right-wing conservative forces remain in power.